Ultra-high specific surface area mesoporous carbon material catalyst and preparation method thereof and butanone-ethylene glycol ketal synthesis method

By using a mesoporous carbon material catalyst with ultra-high specific surface area and loading p-toluenesulfonic acid, the problems of many side reactions and low product purity in the synthesis reaction of butanone-ethylene glycol ketal in the prior art are solved, and higher product purity and environmental benefits are achieved.

CN115957737BActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111193724.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-13
Publication Date
2025-03-28
Estimated Expiration
2041-10-13

AI Technical Summary

Technical Problem

The prior art has problems such as synthesis of butanone-ethylene glycol ketal under homogeneous catalyst catalyzed by homogeneous catalysts, such as many side reactions, low product purity, serious equipment corrosion and environmental pollution.

Method used

An ultra-high specific surface area mesoporous carbon material catalyst is used, which includes p-toluenesulfonic acid supported on the outer surface and inner pore walls of the ultra-high specific surface area mesoporous carbon material to catalyze the synthesis reaction of butanone and ethylene glycol.

Benefits of technology

This catalyst can reduce side reactions, improve product purity, avoid equipment corrosion, and simplify the aftertreatment process, which is conducive to environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115957737B_ABST
    Figure CN115957737B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of catalyst synthesis, and discloses an ultra-high specific surface area mesoporous carbon material catalyst, a preparation method thereof, and a butanone-ethylene glycol acetal synthesis method. The catalyst comprises an ultra-high specific surface area mesoporous carbon material, and p-toluenesulfonic acid is loaded on the outer surface, inner pore wall, and ball center of the ultra-high specific surface area mesoporous carbon material. The specific surface area of ​​the ultra-high specific surface area mesoporous carbon material is 2000-3500m 2 / g, pore volume 0.3-3cm 3 / g, and the average pore size is 2-15nm. The catalyst can reduce side reactions, improve product purity, and be environmentally friendly when used in the synthesis reaction of butanone-ethylene glycol acetal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst synthesis, and in particular to an ultra-high specific surface area mesoporous carbon material catalyst and a preparation method thereof, as well as a butanone-ethylene glycol ketal synthesis method. Background Art

[0002] Butanone-ethylene glycol ketal has a special fragrance and can be used in flavors. It can also be used as an intermediate or solvent for organic synthesis (Fragrance Chemistry. Beijing: Light Industry Press. 1984.250, NH Bratus; Synthesis of butanone-ethylene glycol ketal catalyzed by silicotungstic acid doped polyaniline catalyst, Chemical Reagents, 2005, 27 (2), 121-123, Yang Shuijin; Tong Wenlong; Sun Jutang). Its traditional synthesis method is to synthesize it under the catalysis of homogeneous catalyst inorganic acid, but this method has many side reactions, low product purity, serious equipment corrosion, and a large amount of acidic wastewater in the post-treatment, causing environmental pollution. Therefore, if a heterogeneous catalyst with good catalytic effect is selected to replace the homogeneous catalyst inorganic acid, it can not only avoid the above defects, but also make the homogeneous catalysis heterogeneous.

[0003] Therefore, it is of great significance to study and develop a catalyst for the synthesis reaction of butanone-ethylene glycol ketal. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art in which butanone-ethylene glycol ketal is synthesized under the catalysis of a homogeneous catalyst, such as many side reactions, low product purity and serious equipment corrosion, and to provide an ultra-high specific surface area mesoporous carbon material catalyst and a preparation method thereof and a butanone-ethylene glycol ketal synthesis method. When the catalyst is used in the butanone-ethylene glycol ketal synthesis reaction, the side reactions can be reduced, the product purity can be improved, and the environment is beneficial.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides an ultra-high specific surface area mesoporous carbon material catalyst, wherein the catalyst comprises an ultra-high specific surface area mesoporous carbon material and p-toluenesulfonic acid is loaded on the outer surface, inner pore wall and ball center of the ultra-high specific surface area mesoporous carbon material, wherein the specific surface area of ​​the ultra-high specific surface area mesoporous carbon material is 2000-3500m 2 / g, pore volume 0.3-3.0cm 3 / g, and the average pore size is 2-15nm.

[0006] The second aspect of the present invention provides a method for preparing the aforementioned catalyst, wherein the preparation method comprises: contacting an ultra-high specific surface area mesoporous carbon material with a p-toluenesulfonic acid solution for reaction, filtering and drying the reaction product to obtain an ultra-high specific surface area mesoporous carbon material catalyst.

[0007] The third aspect of the present invention provides a method for synthesizing butanone-ethylene glycol acetal, wherein the synthesis method comprises: in the presence of the above-mentioned catalyst, contacting butanone and ethylene glycol to carry out a synthesis reaction, cooling the obtained reaction solution to room temperature, and then centrifuging to obtain a liquid product butanone-ethylene glycol acetal.

[0008] Through the above technical scheme, the ultra-high specific surface area mesoporous carbon material has a large specific surface area, a large pore diameter, and a large pore volume; the ultra-high specific surface area mesoporous carbon material catalyst of the present invention has the advantages of high selectivity, low cost, and easy separation. It is used to catalyze butanone and ethylene glycol to obtain an important industrial raw material-butanone-ethylene glycol acetal, an intermediate or solvent in synthetic flavors or organic synthesis. It has the catalytic performance of a homogeneous catalyst-concentrated sulfuric acid, and has the advantages of no corrosion to instruments, few side reactions, simple post-treatment process, and the catalyst can be repeatedly used. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is a scanning electron microscope image of the ultra-high specific surface area mesoporous carbon material catalyst prepared in Example 1 of the present invention;

[0010] Figure 2 This is a comparison diagram of the XRD structures of the ultra-high specific surface area mesoporous carbon material (a) and the ultra-high specific surface area mesoporous carbon material catalyst (b). DETAILED DESCRIPTION

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0012] The first aspect of the present invention provides an ultra-high specific surface area mesoporous carbon material catalyst, wherein the catalyst comprises an ultra-high specific surface area mesoporous carbon material and p-toluenesulfonic acid is loaded on the outer surface, inner pore wall and ball center of the ultra-high specific surface area mesoporous carbon material, wherein the specific surface area of ​​the ultra-high specific surface area mesoporous carbon material is 2000-3500m 2 / g, pore volume 0.3-3.0cm 3 / g, and the average pore size is 2-15nm.

[0013] The inventors of the present invention have found that ultra-high specific surface area mesoporous carbon materials are a new type of non-silicon-based mesoporous materials, which have huge specific surface area and pore volume, and the pore diameter is in the mesoporous range.

[0014] According to the present invention, preferably, the specific surface area of ​​the ultra-high specific surface area mesoporous carbon material is 2500-3000m 2 / g, pore volume is 1.0-2.0cm 3 / g, and the average pore size is 10-14nm. In the present invention, the ultra-high specific surface area mesoporous carbon material specified above is used to achieve uniform dispersion of active components by utilizing the high specific surface area and large pore volume of the mesoporous carbon material.

[0015] According to the present invention, based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material is 40-80% by weight, and the content of the p-toluenesulfonic acid is 20-60% by weight; preferably, based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material is 50-70% by weight, and the content of the p-toluenesulfonic acid is 30-50% by weight. In the present invention, the content of the ultra-high specific surface area mesoporous carbon material and the p-toluenesulfonic acid is limited to the aforementioned range, which can more fully exert the structural advantages of the ultra-high specific surface area mesoporous carbon material and improve the performance of the catalyst.

[0016] According to the present invention, the specific surface area of ​​the catalyst is 1200-2800m 2 / g, pore volume 0.1-2.5cm 3 / g, with an average pore size of 1-13nm; preferably, the specific surface area of ​​the catalyst is 1400-2000m 2 / g, pore volume 0.8-1.5cm 3 / g, with an average pore size of 7-11nm. It is very suitable for catalytic reactions involving large molecules.

[0017] The second aspect of the present invention provides a method for preparing the aforementioned catalyst, wherein the preparation method comprises: contacting an ultra-high specific surface area mesoporous carbon material with a p-toluenesulfonic acid solution for reaction, filtering and drying the reaction product to obtain an ultra-high specific surface area mesoporous carbon material catalyst.

[0018] According to the present invention, the p-toluenesulfonic acid solution can be an aqueous solution, an ethanol solution, a methanol solution, an isopropanol solution, a benzene solution or an ether solution of p-toluenesulfonic acid, preferably an aqueous solution, an ethanol solution or a methanol solution.

[0019] According to the present invention, the mass concentration of the toluenesulfonic acid solution is 0.1-20.0%, preferably 0.2-10.0%.

[0020] According to the present invention, the contact reaction conditions include: the temperature can be 30-120° C., preferably 40-90° C.; the time can be 0.5-20 h, preferably 2-10 h.

[0021] According to the present invention, the weight ratio of the ultra-high specific surface area mesoporous carbon material to the toluenesulfonic acid solution is 1:(2-100), preferably 1:(5-50).

[0022] According to the present invention, the drying treatment conditions include: temperature of 60-130° C., time of 1-20 h; preferably, temperature of 80-130° C., time of 3-20 h.

[0023] The third aspect of the present invention provides a method for synthesizing butanone-ethylene glycol acetal, wherein the synthesis method comprises: in the presence of the above-mentioned catalyst, contacting butanone and ethylene glycol to carry out a synthesis reaction, cooling the obtained reaction solution to room temperature, and then centrifuging to obtain a liquid product butanone-ethylene glycol acetal.

[0024] According to the present invention, the molar ratio of butanone to ethylene glycol is 1:(0.5-10);

[0025] According to the present invention, the reaction conditions include: temperature of 100-150° C., time of 1-72 h; preferably, temperature of 110-140° C., time of 2-10 h.

[0026] According to the present invention, the synthesis method further comprises drying the solid phase product obtained by centrifugal separation to obtain a recovered catalyst, wherein the drying conditions include: a temperature of 25-200°C and a time of 1-24 hours.

[0027] According to the present invention, the ultra-high specific surface area mesoporous carbon material catalyst of the present invention is used as a catalyst to catalyze the reaction of butanone and ethylene glycol, the ethylene glycol content is 13-15%, and the butanone-ethylene glycol acetal content of the product is 67-70%. When the catalyst recovered after the above reaction is reused, the ethylene glycol content is 9-12%, and the butanone-ethylene glycol acetal content is 59-65%. However, after the catalytic reaction of acetic acid and n-butanol without any catalyst under the same ratio conditions, no butanone-ethylene glycol acetal product appears.

[0028] According to a preferred embodiment of the present invention, a method for synthesizing butanone-ethylene glycol ketal comprises:

[0029] The reaction uses butanone and ethylene glycol as the reaction raw materials, in molar ratio,

[0030] Butanone:ethylene glycol = 1:0.5-10,

[0031] Using the above-mentioned ultra-high specific surface area mesoporous carbon material catalyst as a catalyst,

[0032] The reaction is stirred at 100-150°C for 1-72 hours, and after the reaction solution is cooled to room temperature, it is centrifuged to obtain a liquid product: butanone-ethylene glycol acetal;

[0033] The solid phase product separated by centrifugation is vacuum dried at 25-200° C. for 1-24 hours to obtain a recovered catalyst.

[0034] Butanone-ethylene glycol ketal has a special aroma and can be used in the synthesis of flavors or as an intermediate or solvent in organic synthesis.

[0035] The present invention will be described in detail below through examples.

[0036] In the following examples and comparative examples:

[0037] The XRD spectrum of the sample was obtained on an X'Pert MPD X-ray powder diffractometer produced by Philips, CuKα radiation, λ=0.154178nm, scanning range 2θ=0.5°~10°. The pore structure parameter analysis of the sample was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA. The sample was vacuum degassed at 350°C for 4 hours before measurement, and the specific surface area of ​​the sample was calculated by the BET method, and the pore volume was calculated by the BJH model. The scanning electron microscope image of the sample was obtained on an XL-30 field emission environmental scanning electron microscope produced by FEI, USA.

[0038] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0039] The reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd. and were of analytical purity.

[0040] Example 1

[0041] This example is intended to illustrate the preparation of a mesoporous carbon material catalyst having an ultra-high specific surface area.

[0042] 1 gram of ultra-high specific surface area mesoporous carbon material a and 10 g of 8% p-toluenesulfonic acid ethanol solution were mixed, stirred at 40°C for 10 hours, and filtered to obtain a solid product. The solid product was dried at 100°C for 8 hours to obtain an ultra-high specific surface area mesoporous carbon material catalyst A loaded with p-toluenesulfonic acid.

[0043] Wherein, based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material is 55.6% by weight, and the content of the p-toluenesulfonic acid is 44.4% by weight.

[0044] The pore structure parameters of the ultra-high specific surface area mesoporous carbon material a and the ultra-high specific surface area mesoporous carbon material catalyst A are listed in Table 1.

[0045] Figure 1This is a scanning electron microscope image of the ultra-high specific surface area mesoporous carbon material catalyst A. Figure 1 It can be seen that the microscopic morphology of the ultra-high specific surface area mesoporous carbon material catalyst A is porous strip-like and arranged neatly and evenly.

[0046] Figure 2 This is a comparison diagram of the XRD structures of ultra-high specific surface area mesoporous carbon material a and ultra-high specific surface area mesoporous carbon material catalyst A. From the small-angle peaks appearing in the XRD spectrum, it can be seen that ultra-high specific surface area mesoporous carbon material a has three obvious diffraction signals between 0.5-2.0°, indicating that the material has a typical hexagonal mesoporous structure. The position of the diffraction signal of ultra-high specific surface area mesoporous carbon material catalyst A is similar to that of ultra-high specific surface area mesoporous carbon material a, but the peak intensity is significantly reduced. This shows that after loading p-toluenesulfonic acid, the mesoporous carbon material still maintains a typical mesoporous structure, and the loaded p-toluenesulfonic acid enters the mesoporous channel, resulting in a decrease in signal intensity.

[0047] Example 2

[0048] This example is intended to illustrate the preparation of a mesoporous carbon material catalyst having an ultra-high specific surface area.

[0049] 1 gram of ultra-high specific surface area mesoporous carbon material B and 21.5 g of 2% aqueous solution of p-toluenesulfonic acid were mixed, stirred at 70°C for 4 hours, and filtered to obtain a solid product. The solid product was dried at 130°C for 3 hours to obtain an ultra-high specific surface area mesoporous carbon material catalyst B loaded with p-toluenesulfonic acid.

[0050] Wherein, based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material is 70 weight %, and the content of the p-toluenesulfonic acid is 30 weight %.

[0051] Example 3

[0052] This example is intended to illustrate the preparation of a mesoporous carbon material catalyst having an ultra-high specific surface area.

[0053] 1 gram of ultra-high specific surface area mesoporous carbon material C and 10 g of 10% p-toluenesulfonic acid methanol solution were mixed, stirred at 90°C for 2 hours, and filtered to obtain a solid product. The solid product was dried at 80°C for 20 hours to obtain an ultra-high specific surface area mesoporous carbon material catalyst C loaded with p-toluenesulfonic acid.

[0054] Wherein, based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material is 50 weight %, and the content of the p-toluenesulfonic acid is 50 weight %.

[0055] Table 1

[0056] sample <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore ​​size (nm) Mesoporous carbon materials 3000 2.0 14 Mesoporous carbon materials 2780 1.6 12 Mesoporous carbon materials 2500 1.0 10 Catalyst A 2000 1.5 11 Catalyst B 1750 1.2 9 Catalyst C 1400 0.8 7

[0057] Example 4

[0058] This example is to illustrate the preparation of butanone-ethylene glycol ketal.

[0059] The ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1 was vacuum dried at 150°C for 6 hours, cooled to room temperature, 0.3 g was weighed, and 21.6 g of butanone and 22.3 g of ethylene glycol were weighed and put into a 100 ml three-necked flask in sequence, and stirred at 120°C for 4 hours. After cooling to room temperature, the mixture was centrifuged and the reaction product liquid composition was analyzed by gas chromatography, with an ethylene glycol content of 15%, and a product butanone-ethylene glycol acetal content of 70%.

[0060] Example 5

[0061] This example is to illustrate the preparation of butanone-ethylene glycol ketal.

[0062] The ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1 was dried at a temperature of 120°C for 18 hours to obtain a recycled ultra-high specific surface area mesoporous carbon material catalyst. After vacuum drying at 150°C for 6 hours, 0.3 g was weighed, and then 21.6 g of butanone and 22.3 g of ethylene glycol were weighed and put into a 100 ml three-necked flask in sequence, and stirred at 120°C for 4 hours. After cooling to room temperature, centrifugation was performed, and the reaction product liquid components were analyzed by gas chromatography. The ethylene glycol content was 12%, and the product butanone-ethylene glycol acetal content was 65%.

[0063] The catalyst recovered after the above reaction has an ethylene glycol content of 10% and a butanone-ethylene glycol acetal content of 60% when reused.

[0064] Example 6

[0065] This example is to illustrate the preparation of butanone-ethylene glycol ketal.

[0066] Butanone-ethylene glycol acetal was prepared in the same manner as in Example 4, except that "the ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1" was replaced with "the ultra-high specific surface area mesoporous carbon material catalyst B prepared in Example 2".

[0067] The results showed that the ethylene glycol content was 14%, and the content of the product butanone-ethylene glycol acetal was 68%.

[0068] Example 7

[0069] This example is to illustrate the preparation of butanone-ethylene glycol ketal.

[0070] Butanone-ethylene glycol acetal was prepared in the same manner as in Example 5, except that "the ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1" was replaced by "the ultra-high specific surface area mesoporous carbon material catalyst B prepared in Example 2".

[0071] The results showed that the ethylene glycol content was 11%, and the content of the product butanone-ethylene glycol acetal was 63%.

[0072] The catalyst recovered after the above reaction has an ethylene glycol content of 9% and a butanone-ethylene glycol acetal content of 59% when reused.

[0073] Example 8

[0074] This example is to illustrate the preparation of butanone-ethylene glycol ketal.

[0075] Butanone-ethylene glycol acetal was prepared in the same manner as in Example 4, except that "the ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1" was replaced with "the ultra-high specific surface area mesoporous carbon material catalyst C prepared in Example 3".

[0076] The results showed that the ethylene glycol content was 13%, and the content of the product butanone-ethylene glycol acetal was 67%.

[0077] Example 9

[0078] This example is to illustrate the preparation of butanone-ethylene glycol ketal.

[0079] Butanone-ethylene glycol acetal was prepared in the same manner as in Example 5, except that "the ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1" was replaced with "the ultra-high specific surface area mesoporous carbon material catalyst C prepared in Example 3".

[0080] The results showed that the ethylene glycol content was 11%, and the content of the product butanone-ethylene glycol acetal was 62%.

[0081] The catalyst recovered after the above reaction has an ethylene glycol content of 8% and a butanone-ethylene glycol acetal content of 58% when reused.

[0082] Comparative Example 1

[0083] Weigh 21.6 g of n-butanol and 22.3 g of acetic acid and put them into a 100 ml three-necked flask in turn. Stir at 120° C. for 4 hours. After cooling to room temperature, centrifuge and analyze the reaction product liquid composition by gas chromatography. No product appears.

[0084] Comparative Example 2

[0085] The butanone-ethylene glycol acetal was prepared in the same manner as in Example 4, except that the "ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1" was replaced with "ordinary mesoporous carbon material having a specific surface area of ​​874 m 2 / g, pore volume 0.6cm 3 / g, and the average pore size is 5nm".

[0086] As a result, the ethylene glycol content was 6%, and the content of the product butanone-ethylene glycol acetal was 50%.

[0087] Comparative Example 3

[0088] Butanone-ethylene glycol acetal was prepared in the same manner as in Example 4, except that "the ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1" was replaced by "catalyst D, which is not loaded with p-toluenesulfonic acid but loaded with zinc chloride".

[0089] As a result, the ethylene glycol content was 4%, and the content of the product butanone-ethylene glycol ketal was 44%.

[0090] Comparative Example 4

[0091] Butanone-ethylene glycol acetal was prepared according to the same method as in Example 4, except that "the ultra-high specific surface area mesoporous carbon material catalyst A prepared in Example 1" was replaced by "ultra-high specific surface area mesoporous carbon material catalyst E, and based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material a is 88 weight %, and the content of p-toluenesulfonic acid is 12 weight %".

[0092] As a result, the ethylene glycol content was 5%, and the content of the product butanone-ethylene glycol acetal was 46%.

[0093] The above results show that the catalyst prepared by the method of the present invention has a significantly better effect in the synthesis reaction of butanone-ethylene glycol ketal. Compared with conventional catalysts, the ultra-high specific surface area mesoporous carbon material catalyst can reduce side reactions and improve product purity.

[0094] Since the catalyst of the present invention was not used in Comparative Example 1, no product was generated.

[0095] In Comparative Example 2, ordinary mesoporous carbon material is used as the catalyst carrier, resulting in uneven distribution of active components, resulting in a low yield of the target product.

[0096] In Comparative Example 3, the catalyst does not carry p-toluenesulfonic acid, but carries zinc chloride as an active component. Since the catalytic activity of zinc chloride is lower than that of p-toluenesulfonic acid of the same weight, the yield of the target product is low.

[0097] In Comparative Example 4, the content of the carrier in the catalyst is too high, and the content of the active component p-toluenesulfonic acid is too low. Due to the insufficient active components in the reaction, the yield of the target product is low.

[0098] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A mesoporous carbon material catalyst with ultra-high specific surface area, characterized in that: The catalyst comprises an ultra-high specific surface area mesoporous carbon material and p-toluenesulfonic acid is loaded on the outer surface, inner pore wall and ball center of the ultra-high specific surface area mesoporous carbon material, wherein the specific surface area of ​​the ultra-high specific surface area mesoporous carbon material is 2000-3500m 2 / g, pore volume 0.3-3cm 3 / g, and the average pore size is 2-15nm.

2. The catalyst according to claim 1, wherein The specific surface area of ​​the ultra-high specific surface area mesoporous carbon material is 2500-3000m 2 / g, pore volume is 1-2cm 3 / g, and the average pore size is 10-14nm.

3. The catalyst according to claim 1, wherein Based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material is 40-80% by weight, and the content of the p-toluenesulfonic acid is 20-60% by weight.

4. The catalyst according to claim 3, wherein Based on the total weight of the catalyst, the content of the ultra-high specific surface area mesoporous carbon material is 50-70% by weight, and the content of the p-toluenesulfonic acid is 30-50% by weight.

5. The catalyst according to any one of claims 1 to 4, wherein The specific surface area of ​​the catalyst is 1200-2800m 2 / g, pore volume 0.1-2.5cm 3 / g, and the average pore size is 1-13nm.

6. The catalyst according to claim 5, wherein The specific surface area of ​​the catalyst is 1400-2000m 2 / g, pore volume 0.8-1.5cm 3 / g, and the average pore size is 7-11nm.

7. A method for preparing the catalyst according to any one of claims 1 to 6, characterized in that: The preparation method comprises: contacting a mesoporous carbon material with an ultra-high specific surface area with a p-toluenesulfonic acid solution for reaction, filtering and drying the reaction product to obtain an ultra-high specific surface area mesoporous carbon material catalyst.

8. The preparation method according to claim 7, wherein: The p-toluenesulfonic acid solution is an aqueous solution, an ethanol solution, a methanol solution, an isopropanol solution, a benzene solution or an ether solution of p-toluenesulfonic acid; And / or, the mass concentration of the toluenesulfonic acid solution is 0.1-20%; And / or, the conditions for the contact reaction include: temperature of 30-120° C.; time of 0.5-20 h; And / or, the weight ratio of the ultra-high specific surface area mesoporous carbon material to the toluenesulfonic acid solution is 1:(2-100).

9. The preparation method according to claim 8, wherein: The toluenesulfonic acid solution is an aqueous solution, an ethanol solution or a methanol solution; And / or, the mass concentration of the toluenesulfonic acid solution is 0.2-10%; And / or, the conditions for the contact reaction include: temperature of 40-90° C.; time of 2-10 h; And / or, the weight ratio of the ultra-high specific surface area mesoporous carbon material to the toluenesulfonic acid solution is 1:(5-50).

10. A method for synthesizing butanone-ethylene glycol ketal, characterized in that: The synthesis method comprises: in the presence of the catalyst described in any one of claims 1 to 6, contacting butanone and ethylene glycol to carry out a synthesis reaction, cooling the obtained reaction solution to room temperature, and then centrifuging to obtain a liquid product butanone-ethylene glycol acetal.

11. The method according to claim 10, wherein: The molar ratio of butanone to ethylene glycol is 1:(0.5-10); And / or, the reaction conditions include: temperature of 100-150° C., time of 1-72 h.

12. The method according to claim 10 or 11, wherein: The synthesis method further comprises drying the solid phase product obtained by centrifugal separation to obtain a recovered catalyst.

13. The method according to claim 12, wherein: The drying conditions include: temperature of 25-200° C. and time of 1-24 h.

Citation Information

Patent Citations

  • Loaded zinc trifluoromethanesulfonate catalyst, its preparation method, and preparation method of butanone-glycol ketal

    CN102451756A

  • Preparation method for mesoporous carbon-based solid acid catalyst and application of mesoporous carbon-based solid acid catalyst

    CN103691454A